'A perverse quest for meaning': false witness in Vietnam and beyond. Issue 5 (3rd September 2017) - Caruth, Cathy
Abstract: This essay interprets Robert Jay Lifton's writing on Vietnam veterans as a thinking of history in terms of 'false witness'. Lifton conceives of a form of history that perpetuates its own erasure and of a new form of witness that emerges from this very annihilation.